보건소 간호사의 직무몰입 분석 - 문영희(Young Hee Mun); 정영숙(Young Sook Chung) (지역사회간호학회지, 1996)
This study was carried out to explore the direction of job involvement of public health nurses and explore the way for improving services of public health center in Korea. The subjects were consisted of 164 nurses who were working at public health centers in Chonbuk. The data were collected by self-reporting questionnaire from Jan. 15 to Jan. 27, 1996. The instrument used in this study was Likert-type scale which Job Involvement Scale developed by Kanungo. The questionnaires of organizational and job characteristic were made through reviewing literatures. The data were analyzed by frequency, percentage, t-test, one-way ANOVA, Scheffe test, and Pearson's correlation coefficient with SPSSPC+ program. Major findings were as follows : 1. Mean scores for job involvement were 3.0879 on a 5 point scale. 2. In the personal variables, professional experience(t=-2.18, p=.031), position(t=2.34, p=.021), and age(F=-1.94, p=.038) were statistically significant in job involvement. 3. The variables to job characteristic were statistically significant in job involvement: job challenge (r=.4785, p=.000), role ambiguity (r=-.3141, p=.000), task significance (r=.2714, p=.000), and role conflict(r=-.2166, p=.003). 4. The variables to organizational characteristic were statistically significant in job involvement : formalization(r=.3184, p=.000) and human centered organizational characteristic (r=.2450, p=.001).